Symposium overview: breaking the links between conflict and food insecurity in complex emergencies - Messer, Ellen; Cohen, Marc J. (2002)
This article gives an overview of the papers and perspectives from the Symposium on Nutrition in the Context of Crisis and Conflict. The papers addressed the three dimensions of nutrition : food, health, and care and the three aspects of food security: availability, access, and utilization. On the whole, the presentations did not address conceptual or theoretical questions, but presented some case studies on livestock protection as examples of successful strategies for preventing or mitigating the impacts of conflict.